Critical Factors Dictating Reversibility of the Zinc Metal Anode. Issue 4 (17th April 2020) - Ma, Lin; Schroeder, Marshall A.; Pollard, Travis P.; Borodin, Oleg; Ding, Michael S.; Sun, Ruimin; Cao, Longsheng; Ho, Janet; Baker, David R.; Wang, Chunsheng; Xu, Kang
Abstract : With high energy density and improved safety, rechargeable battery chemistries with a zinc (Zn) metal anode offer promising and sustainable alternatives to those based on lithium metal or lithium‐ion intercalation/alloying anode materials; however, the poor electrochemical reversibility of Zn plating/stripping, induced by parasitic reactions with both aqueous and non‐aqueous electrolytes, presently limits the practical appeal of these systems. Although recent efforts in rechargeable Zn metal batteries (RZMBs) have achieved certain advancements in Zn metal reversibility, as quantified by the Coulombic efficiency (CE), a standard protocol for CE has not been established, and results across chemistries and systems are often conflicting. More importantly, there is still an insufficient understanding regarding the critical factors dictating Zn reversibility. In this work, a rigorous, established protocol for determining CE of lithium metal anodes is transplanted to the Zn chemistry and is used for systematically examining how a series of factors including current collector chemistry, current density, temperature, and the upper voltage limit during stripping affect the measured reversibility of different Zn electrolytes. With support from density functional theory calculations, this standardized Zn CE protocol is then leveraged to identify an important correlation between electrolyte solvation strength toward Zn 2+ and the measured Zn CE in the corresponding electrolyte, providing new guidance for future development and evaluation of Zn electrolytes. Abstract : Coulombic Efficiency (CE) measurements can be used to predict the lifetime of a Zn metal anode, but the accuracy of these predictions depends on the test method and selection of parameters realistic to rechargeable Zn metal batteries. Transplanting a "reservoir" CE protocol developed for lithium metal batteries to the Zn chemistry, this study examines how a series of factors including current density, temperature, substrate chemistry, and the upper cut‐off voltage limit during stripping affect Zn CE in different electrolytes. These results are leveraged to identify an important correlation between electrolyte solvation strength toward Zn 2+ and CE with support from density functional theory calculations.